Coach's Strategy in Instilling Hard Work Character Education in Gymnastics Trainees at the Persani Training Center, Malang City - Maulidya, Annisa’ Nur; Rasyad, Ach; Listyaningrum, R Anggia (Proceedings Series of Educational Studies, 2024)
This research describes the character of hard work that is manifested in gymnastics trainees, describes the strategies and supporting and inhibiting factors of trainers in instilling hard work character education in gymnastics trainees. The research was conducted using a qualitative research approach with a case study type. This research was conducted at the Persani gymnastics training ground in Malang City. The data collection technique used in this research was in-depth interview techniques, observation and documentation studies. Data analysis techniques are carried out through the stages of data reduction, data presentation, and drawing conclusions. To ensure the validity of this research, researchers used source triangulation, technical triangulation, and time triangulation techniques. This research shows that the character of hard work is manifested in gymnastics training participants, which is demonstrated by a disciplined attitude, never giving up, and being serious about doing their work. The strategies used by trainers in instilling educational character are through a serious but relaxed approach, reflection, example, providing motivation and giving rewards. Supporting factors for trainers in instilling hard work character education in gymnastics trainees include cooperation with parents, adequate facilities, and a positive training environment. Meanwhile, the inhibiting factors are school schedules and gymnastics trainees who are dating. Keywords: Training Strategies; Gymnastics; Character Education; Hard Work